(3CMcGe fLhejI JJYdb HeUQs
(3ChdgG (B:s
(3GdMeO ddg efTF GdSehGJ hQGaYgG HbOQJg hRjf GdSeGA HRjfI GdchGcH ahbY GdfXQ hGdebGHdI ai fMhS GdchGcH s
(3BNQgG (B:s
(3hJaYd CHhGH GdeOjfI SHYI , aGddg Chdi HGdMjd Yf GdedC hJfbGO Ndb Gddg hJbGe McGe GdfHi JeJ gPg GdfSNI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdHdOjI (B_ (3GdCScfOQjI (B(1757(3H(B) s
Keywords: (3Gdadcs